Integrating biophilic design approach to sports architecture (ARTEKS : Jurnal Teknik Arsitektur, 2026)
The integration of biophilic design principles in sports architecture is rooted in the theory of biophilia and human innate affinity for nature, offering a compelling architectural football academy solution for better performance. This architectural approach seeks to strategically connect buildings, spaces and users more closely to nature, creating a productive, healthy and sustainable communal built environment. The study aims to investigate how integration of biophilic strategies can improve environmental sustainability, user well-being, and functional spatial performance in athletic facilities. Key objectives include identifying existing biophilic design elements, evaluating their impact, and proposing a context-specific framework for improvement. A qualitative methodology was adopted, incorporating site observation, architectural assessment, literature review and case study. Findings reveal partial implementation of biophilic features such as natural lighting, ventilation, and so on, while highlighting gaps in user-centred planning and ecological integration. The study also examines the integration of sustainable biophilic design principles in Leadcity University Football Academy in Oyo State, Nigeria and concludes that a comprehensive, nature-integrated approach can significantly improve athlete experience and environmental outcomes. The study recommends a biophilic design approach tailored to Nigerian sports facilities and policy reforms to incorporate biophilic design principles into national architectural guidelines for sports infrastructure.